Moment method approach to analyze waveguide array radiator with crossed dipole as a near field sensor - M., Suma; M.A, Goutham.; ., Paramesha (International Journal of Engineering and Technology, 2019)
Moment method approach is used to estimate the error encountered by the sensor in the near field and probe measures co-pole and cross-pole voltages at the same time. Conversely, due to several reflections between the waveguide and dipole sensor, near field values are changed. Calculations are done to analyze the absolute sampled co-pole voltage pattern and relative sampled electric field (without probe) pattern in the scan plane, and inaccuracy induced by the sensor is determined. The waveguide reflection coefficient, radiation admittance and susceptance with measuring sensor are reformed with respect to the equivalent values in the absence of the sensor in the near field. Â